2007
DOI: 10.1097/01.opx.0000254035.39055.05
|View full text |Cite
|
Sign up to set email alerts
|

Reading With Optical Magnifiers: Page Navigation Strategies and Difficulties

Abstract: We quantified page navigation strategies and difficulties of people with AMD reading with magnifiers. Retrace, which presents the most common difficulty, is not well predicted by vision measures or magnifier characteristics; future studies should investigate the relationship between motor skills and navigation performance, and the impact of training or devices on reducing retrace navigation difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
2
10
2
3
Order By: Relevance
“…This result is consistent with previous research showing that during near work tasks an increased use of optical enlargement in visual enhancing devices may adversely result in restricted postures [22, 26, 27, 35] that subsequently can lead to increased musculoskeletal complaints as well as balance complaints [15, 17]. …”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous research showing that during near work tasks an increased use of optical enlargement in visual enhancing devices may adversely result in restricted postures [22, 26, 27, 35] that subsequently can lead to increased musculoskeletal complaints as well as balance complaints [15, 17]. …”
Section: Discussionsupporting
confidence: 92%
“…31 However, the motor demands of operating an optical or electronic magnifier can sometimes reduce reading speed. 32 The combined effects on reading performance could be assessed by measuring the ACC with and without the magnifier.…”
Section: Discussionmentioning
confidence: 99%
“…96 Page navigation strategies with optical magnifiers were measured by Bowers and colleagues. 97 They found that vision measures were more strongly associated with forward navigation time than retrace navigation, reflecting the greater degree of visual and cognitive processing that occurs when reading along a line than the minimal processing that occurs during retrace. In general, navigation errors were not well predicted by any of the vision or magnifier measures.…”
Section: Low Vision Trainingmentioning
confidence: 98%
“…In addition, new magnifier users may have difficulty manipulating the magnifier across the page to read (forward movement) and back across the page to find the start of the next line (retrace movement), which is termed page navigation 96 . Page navigation strategies with optical magnifiers were measured by Bowers and colleagues 97 . They found that vision measures were more strongly associated with forward navigation time than retrace navigation, reflecting the greater degree of visual and cognitive processing that occurs when reading along a line than the minimal processing that occurs during retrace.…”
Section: Low Vision Trainingmentioning
confidence: 99%